La condanna cristiana della cupiditas ultionis: Vendetta privata e vendetta attraverso la legge - Neri, Valerio (Tesserae iuris, 2023)
The Christian texts in which the desire for revenge is condemned are mainly late ancient Latin texts, by authors such as Augustine, Ambrose, Leo the Great and the condemnation is justified by two New Testament passages, Mt 6, 12 and Rm 12, 17. The revenge condemned is also that prosecuted through the laws and courts and the attitude of the church towards Roman criminal justice is therefore recalled. The non-Christian precedents, Plato and the Stoics, are analyzed to highlight the characteristics and limits of Christian novelty in this area.